Reproductive Traits and the Physiological Background of the Seasonal Variations in Egyptian Suffolk Ewes under the Conditions of Egypt - Marai, I F M; El-darawany, A A; Abou-Fandoud, E I; Abdel-Hafez, M A M (Annals of Arid Zone, 2016)
The calculated temperature-humidity index indicated absence of heat stress during winter and exposure to very severe heat stress during summer and to severe heat stress during autumn, under the sub-tropical conditions of Egypt. Cervical mucus pH was lower significantly (P<O.O1), while viscosity (spinnbarkiet) and electric resistance (ER) were higher significantly (P<O.O1) in winter than in summer and autumn breeding seasons. Ferning arborization was not affected by season of the year. Glucose, inorganic phosphorus and zinc were higher significantly (P<O.05) in cervical mucus in winter and autumn than in summer breeding season. The progesterone hormone level in urine (efficacious) in ewes at day 21 after mating was higher significantly (P<O.05) in summer than in winter and autumn seasons. Conception rate was higher significantly (P<O.05) in ewes mated in winter and autumn than in those mated in summer breeding season.